The Adventures of Ms. Meta: Developing a Historical Superhero Video Game - Zaidan, Sarah (Gamevironments, 2016)
The Adventures of Ms. Meta (forthc.) uses a combination of brawler and puzzle game mechanics along with the narrative device of time travel to provide players with the means to become active participants in the cultural narrative of the American superhero. Although these larger than life characters are irrefutably fixtures in contemporary popular culture, they exist in constant change; reinvented time after time in accordance with each era's definition of heroism, adapted as media forms evolve. As a game designer with a background in comic book illustration and superhero art history, this article explores my process of developing an experience that engages with the ever-changing relationship between superheroes and American culture. Players assume the role of Ms. Meta, a modern female superhero, in an adventure where every level represents a different age of superhero comics, and the world that produced them. Grounded in academic research, and featuring game mechanics including puzzle-solving and collaboration, I hope to empower players to create their own definition of heroism.